Reengineering of Position and Role of Institution and Policy on Land Rehabilitation - Muhammad Said Didu (Jurnal Keteknikan Pertanian, 2002)
The purpose of land rehabilitation (LR) is to improve of landuse capability. Actually, LR needed participation of many institutions and policies. The objective of this research is to access the role, position, and function of each institution and each policy related to LR. The research methodology is intrepretation Structural Modelling (ISM). The result showed there are 26 institutions and 12 policies related to LR. Department of Forsetry, Environment Non-Government Organization (NGO), and District Department of Forestry have high score driver power and dependensy to LR programs.